Strategic alliances in a globalizing world - Das, T. K. 1938- (Research in strategic alliances., 2011)
Strategic Alliances in a Globalizing World contains contributions by leading scholars in the field of strategic alliance research. The 11 chapters in this volume cover a number of significant topics that speak to the growing role of strategic alliances in a globalizing business world. The chapter topics cover both the broader issues, such as the creation of competitive advantage and expanding into institutionally different countries, and the more focused problems of alliance formation, contractual governance, governance structure choice, the development of alliance capability, the containment of opportunism, relationship management, sensemaking, and the intersection of culture and legitimacy. The chapters include empirical as well as conceptual treatments of the selected topics, and collectively present a wide-ranging review of the noteworthy areas of alliance research in the globalization context.